Herbivore Preference for Native vs. Exotic Plants: Generalist Herbivores from Multiple Continents Prefer Exotic Plants That Are Evolutionarily Naïve - Morrison, Wendy E. (Public Library of Science, 2011)
Enemy release and biotic resistance are competing, but not mutually exclusive, hypotheses addressing the success or failure of non-native plants entering a new region. Enemy release predicts that exotic plants become invasive by escaping their co-adapted herbivores and by being unrecognized or unpalatable to native herbivores that have not been selected to consume them. In contrast, biotic resistance predicts that native generalist herbivores will suppress exotic plants that will not have been selected to deter these herbivores. We tested these hypotheses using five generalist herbivores from North or South America and nine confamilial pairs of native and exotic aquatic plants. Four of five herbivores showed 2.4–17.3 fold preferences for exotic over native plants. Three species of South American apple snails (Pomacea sp.) preferred North American over South American macrophytes, while a North American crayfish Procambarus spiculifer preferred South American, Asian, and Australian macrophytes over North American relatives. Apple snails have their center of diversity in South America, but a single species (Pomacea paludosa) occurs in North America. This species, with a South American lineage but a North American distribution, did not differentiate between South American and North American plants. Its preferences correlated with preferences of its South American relatives rather than with preferences of the North American crayfish, consistent with evolutionary inertia due to its South American lineage. Tests of plant traits indicated that the crayfish responded primarily to plant structure, the apple snails primarily to plant chemistry, and that plant protein concentration played no detectable role. Generalist herbivores preferred non-native plants, suggesting that intact guilds of native, generalist herbivores may provide biotic resistance to plant invasions. Past invasions may have been facilitated by removal of native herbivores, introduction of non-native herbivores (which commonly prefer native plants), or both.